2020
DOI: 10.3389/fphar.2020.598702
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of the Anti-inflammatory Effects of Roflumilast on Human Bronchus: Potentiation by a Long-Acting Beta-2-Agonist

Abstract: Background: Roflumilast is an option for treating patients with severe COPD and frequent exacerbations despite optimal therapy with inhaled drugs. The present study focused on whether the phosphodiesterase (PDE) 4 inhibitor roflumilast and its active metabolite roflumilast N-oxide affect the release of tumor necrosis factor (TNF)-α and chemokines by lipopolysaccharide (LPS)-stimulated human bronchial explants. We also investigated the interactions between roflumilast, roflumilast N-oxide and the β2-agonist for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
(116 reference statements)
0
4
0
Order By: Relevance
“…To evaluate the association of apremilast with downstream JAK/STAT signaling, we evaluated changes in levels of activated (phosphorylated) STAT1 and STAT3 before and after therapy using immunohistochemistry. In addition, we evaluated changes in levels of CCL5, a known PDE-4 target and an inflammatory marker in DM . After therapy, phosphorylation of STAT1 decreased by a mean (SD) of 22.3% (28.3%) positive cells ( P = .09), with a mean (SD) H score decrease of 46.1 (54.9) ( P = .07) (Figure 4A-D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the association of apremilast with downstream JAK/STAT signaling, we evaluated changes in levels of activated (phosphorylated) STAT1 and STAT3 before and after therapy using immunohistochemistry. In addition, we evaluated changes in levels of CCL5, a known PDE-4 target and an inflammatory marker in DM . After therapy, phosphorylation of STAT1 decreased by a mean (SD) of 22.3% (28.3%) positive cells ( P = .09), with a mean (SD) H score decrease of 46.1 (54.9) ( P = .07) (Figure 4A-D).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we evaluated changes in levels of CCL5, a known PDE-4 target and an inflammatory marker in DM. 27,28 After therapy, phosphorylation of STAT1 decreased by a mean (SD) of 22.3% (28.3%) positive cells (P = .09), with a mean (SD) H score decrease of 46.1 (54.9) (P = .07) (Figure 4A-D). Similarly, pSTAT3 levels decreased by a mean (SD) of 13.4% (11.6%) positive cells (P = .03), with a mean (SD) H score decrease of 26.9 (22.9) (P = .02) (Figure 4E-H).…”
Section: Association With Inhibition Of Inflammatory Signaling Pathwa...mentioning
confidence: 99%
“…This immune response is associated with the expression of pro-inflammatory cytokines, fibrosis, oxidative damage and neurodegeneration, contributing to wound-healing failure [ 37 ]. The reduction in ameboid microglia/macrophages is probably due to a direct effect on inflammation by Rof since it has previously been demonstrated that Rof has an anti-inflammatory effect [ 48 , 49 ]. For instance, as seen in the lung, Rof consistently minimizes the release of TNF-α, CCL2, CCL3, CCL4, CCL5 and CXCL9 from human bronchial explants [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in ameboid microglia/macrophages is probably due to a direct effect on inflammation by Rof since it has previously been demonstrated that Rof has an anti-inflammatory effect [ 48 , 49 ]. For instance, as seen in the lung, Rof consistently minimizes the release of TNF-α, CCL2, CCL3, CCL4, CCL5 and CXCL9 from human bronchial explants [ 49 ]. The accumulation of microglia/macrophages in the lesion epicenter plays a significant role in the inflammatory response during secondary injury.…”
Section: Discussionmentioning
confidence: 99%